(untitled) - Mauch, James E. (New York, NY, 2004)
A classic text trusted by both students and advisors meeting the challenges of producing—and, ultimately, publishing—theses and dissertations (T/D), this Fifth Edition views the valuable addition of references to university research libraries and advanced information on websites, online searches, electronic literature, and other modern computer methods as crucial for the successful completion of any T/D.
Keywords: Library science,Dissertations, academic